2020
DOI: 10.3390/ijerph17238731
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality in Quality of Life among Rural Communities in Malaysia: A Case for Immediate Policy Consideration

Abstract: Quality of life (QOL) is a proxy of health and social well-being. Hence, it is vital to assess QOL as it informs the strategies of policymakers to enhance the living conditions in communities. Rural areas in emerging economies are underserved in terms of modern facilities and technologies, which impact QOL. To address this, this study investigated whether income played a role in the QOL of rural residents within emerging economies using a large survey of Malaysian adults above 18 years old. The study extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…The counterevidence point towards the overwhelming effect of age on HRQOL [15,20,[36][37][38], similar to the present study. The implications of an ageing phenomenon include structural changes to families and households, social networks and interaction, leisure, housing and transportation, welfare services and pension, saving and consumption behaviour, and labour markets [39]. Hence, it is imperative to uplift the QOL of the older generation.…”
Section: Discussionmentioning
confidence: 99%
“…The counterevidence point towards the overwhelming effect of age on HRQOL [15,20,[36][37][38], similar to the present study. The implications of an ageing phenomenon include structural changes to families and households, social networks and interaction, leisure, housing and transportation, welfare services and pension, saving and consumption behaviour, and labour markets [39]. Hence, it is imperative to uplift the QOL of the older generation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, a person was deemed to have poor insight when he indicated unawareness, misattribution and inaction, either alone or together. Monthly household income groups were categorized into three categories, which were the bottom 40% (B40), middle 40% (M40) and top 20% (T20), based on the income thresholds provided by the Department of Statistics Malaysia in 2014 [ 24 ]. Full-time HCPS was considered when the pharmacist’s essential duty was to conduct home medication reviews on all working days.…”
Section: Methodsmentioning
confidence: 99%
“…Education, ethnic group or social class, income, and employment are typical indicators of socioeconomic status [19]. Community-based studies from LMICs have revealed the relationship between low socioeconomic status (SES) and common mental disorders [20][21][22][23]. Recent literature revealed that low socioeconomic status was linked to lower health literacy with higher stigma [24,25] and lack of mental health help-seeking [26].…”
Section: Introductionmentioning
confidence: 99%